Pharmacovigilance and Adverse Drug Reaction Reporting in Primary, Secondary, and Tertiary Healthcare: A Review of Practices, Challenges, and Recommendations - Radlović, Aleksandar; Mahmutović, Elvis; Safiye, Teodora (Archives of Pharmacy, 2025)
According to the World Health Organization, pharmacovigilance is a science and activities related to the detection, assessment, understanding, and prevention of adverse effects or any other drug-related problems. Since the underreporting of adverse drug reactions (ADRs) remains a significant global issue, reporting ADRs is essential for the success of pharmacovigilance programs. By systematically monitoring and reporting ADRs at the primary, secondary, and tertiary levels of healthcare, pharmacovigilance plays a crucial role in protecting public health. In addition to facilitating the early identification and prevention of negative consequences, reporting also contributes to improving the quality of healthcare services. This article presents a narrative review aimed at synthesizing available literature and regulatory documents related to pharmacovigilance and ADR reporting across various levels of healthcare, with particular emphasis on the national context in Serbia and relevant international comparisons.
Keywords: pharmacovigilance; adverse drug reactions; healthcare